Long term consolidation study on tropical peta at Pekan, Pahang, Malaysia - Mohd Ikhwan, Ab Kadir (2011)
Peats are formed by disintegration of plant and organic matters. In Malaysia, the area covered by peat deposit is about 3 million hectares or 8% of the total area of Malaysia. Peat has high compressive deformation, very high void ratio and water content and has low shear strength. It is widely regarded as a problematic soil since it poses serious problems in construction due to its long-term consolidation settlements even when subjected to a moderate load. Construction over peat will be subjected to massive primary and long term secondary and even tertiary settlement. This study will be conducted to gain a better understanding about the long term consolidation on tropical peat soil of East Coast of Peninsula Malaysia. The study will focused on the analysis of consolidation behavior of peat soil based on the time-deformation curve obtained from Oedometer Test. Based on this test, we can determine the consolidation time so that we can predict how long the time taken by the soil to settle. In the determination of consolidation time, the first thing we need to know is the consolidation coefficient value and this value may be obtained from Oedometer Test. It was expected that the value of settlement is high since peat is very soft and easily compressed. The study of the long term consolidation of peat soil is important to predict the amount of settlement that will occur to the peat soil in a long time period.